Comparision of tribological behaviour for parts fabricated through fused deposition modelling (FDM) process on abs and 20% carbon fibre PLA. (2020) - Srinivasan, R.; Suresh Babu, B.; Udhaya Rani, V.; Suganthi, M.; Dheenasagar, R.
Abstract: Fused deposition modelling (FDM) is a modern rapid prototyping technique which is used colossally for its ability to build applicable components in an equitable time. It is a 3D printing technique where the constituents are printed by supplementing the heated engineering plastic material layer by layer through a print head nozzle. So far engineered thermoplastics like Acrylonitrile Butadiene Styrene (ABS), carbon fibre poly lactic acid (CFPLA), polyamide, etc were used for parts production in this realm. During the itinerary of process engineering plastics may undergo wear because of the real time processing conditions like high pressure, temperature etc. In this experimental investigation a comparative study on tribological properties was performed on parts fabricated by FDM technique for 20% CFPLA and ABS specimens. The process parameters considered in this study are layer thickness, infill pattern and infill density. A series of Pin-on-disc tests by varying normal load and sliding speed, essentially a materials tribology test is used to screen the materials for the tribological properties (wear rate and coefficient of friction). In this study the layer thickness contribute to the wear at a direct proportion because as the thicker one would last long to wear and reach substrate because of its size. The infill pattern is indirectly proportional to the wear rate.